2D PET Sensitivity Evaluation using a 20cm Diameter Phantom (Bangladesh Journal of Medical Physics, 2013)
A prototype small ring camera "miniPET" with a FOV of 20cm and as a 16-crystal-ring tomograph was constructed by reconfiguring components from a standard medical ECAT PET. Alternate detector modules from the original standard system were used to make the miniPET with a diameter 50% of the original. After calibrating the camera, the sensitivity of the system was measured using a 20cm diameter 68-Ge cylindrical phantom. The aim of the study is to investigate the coincidence events detection performance (sensitivity) of the camera in 2D mode (ring difference ? 3) but without septa using a large size phantom in respect to the camera FOV. Results indicate that the sensitivity measured using the phantom (6.2 cps/kBq) is approximately 30% lower than that measured using a line source of 3mm diameter. The difference can be attributed to attenuation in the phantom. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14663 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 25-28